2003
DOI: 10.1016/s1388-9842(03)00039-4
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of self‐management strategies in a heart failure management programme

Abstract: Background: Multidisciplinary heart failure programs including patient education and self-management strategies such as daily recording of body weight and use of a patient diary decrease hospital readmissions and improve quality of life. However, the degree of uptake of individual components of these programs and their contribution to patient benefit are uncertain. Methods: Patients with heart failure admitted to Auckland Hospital were randomised into the management or usual care groups of the Auckland heart f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
106
2
10

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(119 citation statements)
references
References 31 publications
1
106
2
10
Order By: Relevance
“…However, this does not preclude an impact of age on the results of educational intervention. In our study the mean age of 79 years was higher than in the studies by Jaarsma et al [34] and Wright et al [21] with mean ages of respectively 72 and 73 years.…”
Section: Discussioncontrasting
confidence: 76%
“…However, this does not preclude an impact of age on the results of educational intervention. In our study the mean age of 79 years was higher than in the studies by Jaarsma et al [34] and Wright et al [21] with mean ages of respectively 72 and 73 years.…”
Section: Discussioncontrasting
confidence: 76%
“…Earlier smaller studies also have not shown any convincing evidence for self-management. [33][34][35][36] Therefore, a strategy that minimizes patient responsibility in monitoring and care might be more pragmatic. All strategies should still aim at having a patient-centered care plan along with stressing patient education.…”
Section: Home Monitoring -Is It An Epidemiologically Feasible Solution?mentioning
confidence: 99%
“…A growing trend in healthcare, owing to spiralling costs and the shortage of providers, is an emphasis on self-management strategies or group education sessions for patients with chronic medical conditions 12,13 . This is very different from the traditional treatment model centred around doctor/patient clinic visits.…”
Section: Current Treatment Of Chronic Painmentioning
confidence: 99%